PH measurements of FET-based (bio)chemical sensors using portable measurement system - Voitsekhivska, T.; Zörgiebel, F.; Suthau, E.; Wolter, K. J.; Bock, K.; Cuniberti, Gianaurelio (Giovanni) (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2015)
In this study we demonstrate the sensing capabilities of a portable multiplex measurement system for FET-based (bio)chemical sensors with an integrated microfluidic interface. We therefore conducted pH measurements with Silicon Nanoribbon FET-based Sensors using different measurement procedures that are suitable for various applications. We have shown multiplexed measurements in aqueous medium for three different modes that are mutually specialized in fast data acquisition (constant drain current), calibration-less sensing (constant gate voltage) and in providing full information content (sweeping mode). Our system therefore allows surface charge sensing for a wide range of applications and is easily adaptable for multiplexed sensing with novel FET-based (bio)chemical sensors.
CRIS-Team Scopus Importer:2023-03-20